Citizen Engagement in Sustainability Planning: Patterns and Barriers from Hinton and Wood Buffalo, Alberta, Canada ... - Hallström, Lars K.; Hvenegaard, Glen; Dipa, Susrat Jahan (University of Alberta Library, 2019)
Canada’s Gas Tax Fund is intended to support municipal sustainability initiatives, provided that each applying municipality formulates a form of Integrated Community Sustainability Plan. Both the federal and provincial governments made citizen participation an important requirement of the planning process for creating these sustainability plans. This article’s goal is to describe the nature and challenges of citizen involvement in developing sustainability plans for rural communities in Alberta, Canada. Using the Town of Hinton and the Regional Municipality of Wood Buffalo as case studies, planners, public officials, and sustainability coordinators offered their perceptions of citizen engagement, including stages of involvement, participatory techniques, promoting factors, and challenges. Our results show that sustainability planning was broadly consultative, employed diverse techniques, and respondents welcomed the opportunity to provide input and support for the sustainability plans. Key challenges to ...